Gender and Age: Do They Play a Role in Medical Faculty Students' Perceptions of the Learning Environment Using the DREEM Instrument? - Rika Nilapsari; Mia Kusmiati; Annisa Rahmah Furqaani; Miranti Kania Dewi; Rahma Reza Zakiyah; Mudzakkir Rayyis (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Evaluation and measurement of the learning environment can help improve the quality of education, including by assessing students' perceptions of it. Various internal and external factors will influence students' assessment of the learning environment. One instrument for measuring students' perceptions of the learning environment is the Dundee Ready Education Environment Measure (DREEM). This study aims to analyze the effects of gender and age on students' perceptions of the learning environment at the Faculty of Medicine in Bandung. This study uses primary data collected using the DREEM instrument to examine students' perceptions of the learning environment at the Faculty of Medicine. The subjects of this study were 437 students in the academic phase of the Faculty of Medicine. The research subjects were selected by random sampling. The average score per DREEM domain was then analysed using the Mann-Whitney test because the data were not normally distributed. The results showed that the average scores of female and male students were not significantly different across the DREEM domains (p>0.05). The average score for students aged >20 years was considerably lower in the learning process and lecturer domain than for students aged ≤20 years (p<0.05). In conclusion, age influences students' perceptions of the learning environment at the Faculty of Medicine, while gender does not.